Divulging The Seamy Side Of An Extolled Algerian Educational System: Spotting The Intercultural Cracks Within The Lmd System - Boudjelal Mustapha (My University, 2013)
In a world characterised by diversity in terms of identity, belongings and upbringings, developing some skills that beef up understanding others’ perspectives, approaches and relent some maverick appraisals to reality are badly needed. Interculturality as a term covers these salient competencies that allow their user to communicate successfully in educational settings or face-to face contacts with natives, as it decreases students’ miscreant beaviour and reconciles different cultures
Keywords: Divulging Seamy Side Extolled Algerian Educational System: Spotting intercultural Cracks LMD System